Managing the Past into Future: Materiality and Discourse on Cultural Landscape - Widjaja Martokusomo; Budi Faisal; Huda Nurjanti; Feysa Poetry; Nathania Nadia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Referring to the understanding of landscape as a cultural construct, the notion of the cultural landscape is constituted by its essential elements: system, people, and the landscape itself. The nexus between these elements was philosophically developed in a recent discourse that challenges the separation between cultural and natural heritage. This